Sustainable Logistics and Production in Industry 4. 0 : New Opportunities and Challenges - Grzybowska, Katarzyna, 1974-; Awasthi, Anjali, 1976-; Sawhney, R. S. (Springer, 2020)
This book proposes essential methods, models, and case studies for Sustainable Logistics and Production in Industry 4.0. In addition to identifying and discussing various challenges and future prospects, it also features numerous case studies and quantitative research from different sectors. The authors (which include academics and managers) present insightful tips on the technical, organizational and social aspects of implementing Sustainable Logistics and Production in Industry 4.0. In today's world, changes are coming faster and more unpredictably. Production is becoming more automated, computerized and complex. In short, Industry 4.0 is creating many new opportunities, but at the same time several new challenges. This book offers a valuable resource for all academics and practitioners who want to deepen their knowledge of Sustainable Logistics and Production in Industry 4.0.- Resumé vydavatel
Keywords: logistika (management) -- environmentální aspekty; průmysl 4.0; business logistics -- environmental aspects; industry 4.0; elektronické knihy; případové studie; sborníky; electronic books; papers of several authors; case studies